A modified artificial bee colony for N-Queens problem - Sia, De Long; Emerson, Kong Zee Xin; Lim, Sheng Jian; Ling, Jin Han; Salam, Zailan Arabee bin Abdul (Journal of Applied Technology and Innovation, 2022)
This paper is to solve the N-Queen problems with the implementation of the Artificial Bee Colony Algorithm. A modified Artificial Bee Colony algorithm is introduced in this paper to improve the efficiency and the effectiveness of solving the 64-Queens problem. In this paper, a few parameters of the algorithm are changed and compared to each other during the solving of the N-Queens problem, which leads to a better result. Parameters changed include colony population, trial limit, and shuffle range, which directly affect the algorithm; hence a best parameter combination is found for a 64-Queens problem with improvement.